2022
DOI: 10.1111/jgh.15887
|View full text |Cite
|
Sign up to set email alerts
|

Smart Gene™ as an effective non‐invasive point‐of‐care test to detect Helicobacter pylori clarithromycin‐resistant mutation

Abstract: Background and Aim: Smart Gene ™ was developed based on the concept of point-ofcare genetic testing. We evaluated the detection performance of a reagent for Helicobacter pylori (H. pylori) clarithromycin (CAM)-resistant mutation assessment and determined the association between the results of Smart Gene ™ and those of eradication therapy for H. pylori. Methods: In 2020, the present study was conducted on participants of the H. pylori test and treat project in Saga Prefecture. The submitted stool samples were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Recently, Japanese authors published the results of a study in which Smart Gene™, a method based on the concept of point-of-care genetic testing, was used [74]. The results showed that the detection performance of Smart Gene™ was comparable with that of real-time PCR and sequencing analyses [74].…”
Section: Novelties Of the Maastricht VI Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Japanese authors published the results of a study in which Smart Gene™, a method based on the concept of point-of-care genetic testing, was used [74]. The results showed that the detection performance of Smart Gene™ was comparable with that of real-time PCR and sequencing analyses [74].…”
Section: Novelties Of the Maastricht VI Guidelinesmentioning
confidence: 99%
“…Recently, Japanese authors published the results of a study in which Smart Gene™, a method based on the concept of point-of-care genetic testing, was used [74]. The results showed that the detection performance of Smart Gene™ was comparable with that of real-time PCR and sequencing analyses [74]. Although it was not compared with cultures, mentioned method is considerably shorter than real-time PCR tests, thus making it more appropriate for everyday practice [74].…”
Section: Novelties Of the Maastricht VI Guidelinesmentioning
confidence: 99%
“…The detection of Mycoplasma pneumoniae and coronavirus by Smart Gene™ with pharyngeal swabs shows high reproducibility and useability and allows quick patient triage 8–11 . In addition, the detection of H. pylori by Smart Gene™ with stool proved to be an effective non‐invasive test 12 . The “ H. pylori gene detection POCT reagent,” a reagent for the fully automatic Smart Gene™, allows for the automatic detection of H. pylori and CAM resistance‐associated mutations based on the Qprobe method 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In addition, the detection of H. pylori by Smart Gene™ with stool proved to be an effective non-invasive test. 12 The "H. pylori gene detection POCT reagent," a reagent for the fully automatic Smart Gene™, allows for the automatic detection of H. pylori and CAM resistance-associated mutations based on the Qprobe method. [13][14][15] Our goal was the fast and accurate diagnosis of H. pylori and detection of CAM resistance for the purpose of determining a precise eradication therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation